Lady Jane Grey – prawowita królowa, czy uzurpatorka? Kwestia angielskiej sukcesji w 1553 r. - Kowalska, Zuzanna (Przegląd Nauk Historycznych, 2012)
An article is an attempt to answer the question, whether the proclamation of Lady Jane Grey in July of 1553 was legal, or the Nine Days Queen was an usurp-er. It also includes opinions of English historians concerning this problem. There are two main issues. The first is the role of Duke of Northumberland in an alter-nation of the succession made by Edward VI (the verification of Northumber-land’s Black Legend, according to which a decision of designating his daughter-in-law, Lady Jane, to be Edward’s successor was a result of Duke’s manipulation or even a forgery, in order to maintain his influence). Secondly, there is a question about validity of king Edward’s document, entitled My Device for the Succession, which was signed by the most important figures in realm, but never approved by an act of Parliament.